Microbiota and Mental Health: Decoding the Gut-Brain Axis - Grzelak, Alicja (Quality in Sport, 2024)
Introduction: The gut-brain axis, a communication system between the gastrointestinal tract and the central nervous system, has garnered attention for its influence on mental health and neurological disorders. Central to this interaction is the gut microbiota, a diverse microbial community that regulates various physiological and psychological processes through neural, immune, and endocrine pathways. Purpose of Work: This paper explores the role of the gut microbiota in shaping mental health and its potential involvement in neurological disorders. By systematically reviewing current research, the study aims to provide a comprehensive understanding of microbial mechanisms influencing brain function and their implications for novel therapeutic interventions. State of Knowledge: Evidence suggests that gut microbiota dysbiosis is associated with conditions such as anxiety, depression, autism spectrum disorders, and neurodegenerative diseases. Mechanistic insights reveal microbial production of neurotransmitters, modulation of the immune system, and regulation of the gut-brain barrier as pivotal factors. While preclinical studies and emerging clinical trials demonstrate promising outcomes, variability in study designs and individual microbiota profiles pose challenges. Material and methods: The research methodology entailed a systematic review of the relevant literature, followed by a screening process to identify pertinent studies. The investigation encompassed a comprehensive search across scientific databases, including PubMed and Google Scholar. Summary: The gut-brain axis highlights the intricate relationship between gut microbiota and brain health, offering a paradigm shift in understanding mental health and neurological diseases. Advances in microbiota-targeted therapies, including probiotics and dietary interventions, underscore its potential, though further research is needed to validate clinical efficacy and develop personalized treatment approaches.